2021
DOI: 10.2196/17233
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Relaxation for Patients With a Psychiatric Disorder: Crossover Randomized Controlled Trial

Abstract: Background Virtual reality (VR) relaxation is a promising mental health intervention that may be an effective tool for stress reduction but has hardly been tested in clinical trials with psychiatric patients. We developed an easy-to-use VR self-management relaxation tool (VRelax) with immersive 360° nature videos and interactive animated elements. Objective To investigate the immediate effects of VR relaxation on negative and positive affective states a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 52 publications
3
75
1
3
Order By: Relevance
“…Previously, VR has mainly been applied to patients with PTSD as an exposure to traumatic events, e.g., war [ 19 ]. In accordance with our results, a recent study of VR of nature videos improved feelings of anxiety and stress in patients with severe psychiatric disorders [ 20 ]. However, it cannot be ruled out that a large proportion of the intervention effect can be attributed to nonspecific factors and not to the specific method.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, VR has mainly been applied to patients with PTSD as an exposure to traumatic events, e.g., war [ 19 ]. In accordance with our results, a recent study of VR of nature videos improved feelings of anxiety and stress in patients with severe psychiatric disorders [ 20 ]. However, it cannot be ruled out that a large proportion of the intervention effect can be attributed to nonspecific factors and not to the specific method.…”
Section: Discussionsupporting
confidence: 93%
“…Fewer studies have explored virtual reality treatments beyond exposure therapy, with the exception of skills training, which has also demonstrated positive results 99 . Pilot studies have also shown that virtual reality applications can guide people to learn therapeutic skills such as mindfulness 100‐102 , relaxation 103 and self‐compassion 104,105 . Using virtual reality as a vehicle to deliver experiences that help people develop skills to manage mental health difficulties may increase treatment engagement and efficacy.…”
Section: Tools and Technologiesmentioning
confidence: 99%
“…It is also possible that just “a pleasant getaway” from work produced the reduction in perceived stress. However, what argues against this is that in a previous study we found that VRelax when compared to standard relaxation exercises produces a greater improvement in terms of positive mood states, such as cheerfulness ( Veling et al, 2021 ). The additive effect of VR has been confirmed in a broad range of VR studies.…”
Section: Discussionmentioning
confidence: 88%
“…VR relaxation can support emotion-based coping, as well as meaning-focused coping strategies by leading to a positive affective state and immediate stress reduction ( Veling et al, 2021 ). VR relaxation is easy to use and has an advantage over regular relaxation exercises as it requires far less effort in terms of concentration and attention and leads to a larger increase in positive affect (e.g., happiness, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation